The Cultivation of Students’ Religious Character through Qur’anic Literacy in Private Madrasah Aliyah - Harahap, Sarwedi; Tumiran, Tumiran (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze how Qur’anic literacy serves as a strategic approach to cultivating students’ religious character in private Islamic senior high schools. Specifically, it investigates the processes, methods, and educational practices through which Qur’anic literacy influences students’ moral awareness, discipline, and spiritual integrity. Religious character formation in students is viewed as a fundamental aspect of Islamic education that integrates cognitive, affective, and psychomotor domains rooted in the teachings of the Qur’an and Hadith. In the context of globalization and modern popular culture, this study addresses the challenges faced by educators in reinforcing Islamic values amid competing information flows and moral relativism. Methodology: The research employed a qualitative descriptive approach. Subjects were purposively selected, including the principal, vice principal for curriculum, Islamic Religious Education teachers, and students actively engaged in Qur’anic literacy activities. Data were collected through observation, in-depth interviews, and documentation, then analyzed using Miles and Huberman’s interactive model of data reduction, display, and conclusion drawing. Data validity was ensured through source and method triangulation. Main Findings: The results demonstrate that Qur’anic literacy is a primary instrument for shaping students’ religious character through aspects of faith, worship, and morality. Routine activities such as recitation (tadarus), memorization, and Qur’anic exegesis foster spiritual discipline, courteous behavior, and social awareness. Novelty/Originality of this study: The study highlights the role of teachers as role models, facilitators, and motivators, supported by a curriculum systematically integrating Qur’anic values across subjects. This synergy creates a religious, contextual, and sustainable educational ecosystem, shaping students into morally upright generations.